2021
DOI: 10.1039/d1cp01223a
|View full text |Cite
|
Sign up to set email alerts
|

Size dependence of the dissociation process of spherical hydrate particles via microsecond molecular dynamics simulations

Abstract: The dissociation process of spherical sII mixed methane-propane hydrate particles in liquid hydrocarbon was investigated via microsecond-long Molecular Dynamics simulations. A strong dependence of the melting temperature on the particle...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Third, the decrease in the capillary force upon approaching the temperature of the dissociated region can be explained by the rapid thickening of the QLL. In general, QLL thickens as the temperature increases , and leads to an increasing radius r . Finally, low adhesive forces in the low-temperature region are explained by a vanishing or discontinuous QLL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the decrease in the capillary force upon approaching the temperature of the dissociated region can be explained by the rapid thickening of the QLL. In general, QLL thickens as the temperature increases , and leads to an increasing radius r . Finally, low adhesive forces in the low-temperature region are explained by a vanishing or discontinuous QLL.…”
Section: Resultsmentioning
confidence: 99%
“…However, the origin of adhesion forces for clathrate surfaces is poorly understood. Recently, it was reported that clathrate surfaces are not rigid solids but covered by an intrinsic nanometer-thick quasi-liquid layer (QLL) due to surface premelting. However, to what extent the QLL affects the adhesion force of clathrate surfaces was not understood. Therefore, we carry out force measurements and theoretical modeling to find out how the QLL affects the adhesion of clathrate surfaces to other solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In-depth analysis of the force-versus-distance curve in Figure b indicated that the thickness of this QLL is around 10 nm at −4 °C . This experiment-derived thickness of the QLL is significantly thicker than that of subnanometer observed in simulations. Similar discrepancies are observed for the studies of ice surfaces, for which the reported thickness depends largely on the methods employed (Figure ). Hence, quantifying the thickness of the QLL remains an intrinsic challenge (discussed in the Prospects and Challenges section).…”
Section: Molecular Views Of Hydrate Surfacesmentioning
confidence: 51%
“…Maeda et al indicated that interfacial premelting of hydrate surfaces is a thermodynamically favorable process. , Computer simulations have enabled a close look at the temperature-dependent premelting layer on hydrates and ice (Figure ). Some properties of the QLL such as diffusion coefficient and interfacial tension can be estimated based on computer simulations. A question of fundamental importance is how the surface premelting affects the specific surface free energy (γ sv ) of hydrates. Maeda et al was the first research group attempting to estimate γ sv of hydrates using a semiempirical method .…”
Section: Molecular Views Of Hydrate Surfacesmentioning
confidence: 99%
See 1 more Smart Citation